PRECARIOUSNESS LABOR IN THE URBAN GARBAGE COLLECTION IN PRESIDENTE PRUDENTE/SP: RISKS AND AGGRAVATIONS TO HEALTH OF WORKERS - Ramos da Silva, Joao Vitor [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
The article aims to present the precarious labor reality to which are subject the urban garbage collectors in the city of Presidente Prudente/SP, placing greater emphasis to the risks and aggravations to health of workers involved in this world of work located behind the bins of society. The methodology used in the research was based on the interweaving of secondary data (statistics, documents etc.) and primary data (interviews with the collectors of the city in question). Were accomplished 13 semi-structured interviews with workers of collection, all recorded and transcribed in full. From this information, it is possible to establish a clear connection between work in garbage collection and accidents / injuries suffered by workers in this sector.
Keywords: Labor; garbage collection; worker health